Surface modification method of positive electrode

By mixing and calcining the aluminum source and carbon nanotubes with the high-nickel positive electrode material, the problem of poor capacity retention during recycling of high-nickel positive electrode materials is solved, and higher cycling performance and lower DC resistance are achieved.

CN119673972APending Publication Date: 2025-03-21GEM WUXI ENERGY MATERIAL CO LTD

Patent Information

Application Number
CN202411780806.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing high-nickel positive electrode materials have poor capacity retention rates during recycling, and passivation films are easily formed during charging and discharging, increasing the internal resistance of the battery and reducing the circulation performance.

Method used

By mixing and calcining the aluminum source and carbon nanotubes with the positive electrode material, a surface-modified positive electrode material is formed, the contact between the positive electrode material and the electrolyte is isolated, the circulation performance is improved, and the material's DC resistance and side reaction are reduced through aluminum doping and zirconium doping.

Benefits of technology

The cycling performance and capacity retention rate of the positive electrode material are significantly improved, the DC resistance is reduced, the resistance growth during the cycle is suppressed, and the migration rate of lithium ions is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673972A_ABST
    Figure CN119673972A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a surface modification method of a positive electrode. The surface modification method of the positive electrode provided by the invention comprises the following steps that an aluminum source, a carbon nano tube and the positive electrode are mixed and calcined, the surface-modified positive electrode is obtained, the addition amount of the aluminum source is 300 ppm to 900 ppm, and the addition amount of the carbon nano tube is 300 ppm to 900 ppm according to the mass of the positive electrode. The surface of the positive electrode material is modified by coating the positive electrode material with the carbon nanotubes and the aluminum source, on one hand, contact between the positive electrode material and an electrolyte can be isolated to a great extent, and the cycle performance of the material is improved, and on the other hand, the mixture formed by the carbon nanotubes and the aluminum source has good rapid ion and electron transmission performance, and has good electrochemical performance. The migration rate of lithium ions can be improved, the direct-current resistance of the positive electrode material can be reduced, and meanwhile, the increase of the direct-current resistance in the circulation process is inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, and in particular to a surface modification method for a positive electrode. Background Art

[0002] With the rapid development of electric vehicles, energy storage systems and portable electronic devices, the requirements for recyclable battery performance are getting higher and higher. High-nickel positive electrode materials with the characteristics of high energy density and low metal element cost have become a popular choice for positive electrode materials. Among them, high-nickel ternary nickel cobalt aluminum oxide (Ni≥60) is one of the most widely circulated lithium-ion battery positive electrode materials on the market. Its high thermal stability and high energy density are very popular. However, on the one hand, high-nickel positive electrode materials are prone to side reactions with electrolytes under high voltage (4.3V) conditions, resulting in electrolyte decomposition and formation of solid electrolyte interface (SEI) film. The formation of SEI film consumes active lithium, increases internal resistance, and reduces battery cycle performance. On the other hand, during the charge and discharge process of high-nickel positive electrode materials, transition metal ions such as nickel, cobalt, and manganese may dissolve into the electrolyte. These metal ions will be deposited on the surface of the negative electrode to form a passivation film, further increasing the internal resistance of the battery and reducing cycle performance.

[0003] The prior art discloses a composite positive electrode material, which uses a first coating layer to coat a first positive electrode core, and a second coating layer to coat a second positive electrode material core, wherein the first coating layer is a MOF material and the second coating layer is a metal oxide, which can avoid side reactions between the solid electrolyte and the positive electrode material and improve the ionic conductivity, but the capacity retention rate is not ideal during the cycle. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect of poor capacity retention rate of materials during cyclic use in the prior art, thereby providing a surface modification method for a positive electrode.

[0005] To this end, the present invention provides a method for surface modification of a positive electrode, comprising the following steps: mixing an aluminum source, carbon nanotubes and a positive electrode, and calcining to obtain a surface-modified positive electrode, wherein the addition amount of the aluminum source is 300ppm-900ppm, and the addition amount of the carbon nanotubes is 300ppm-900ppm, based on the mass of the positive electrode.

[0006] In some embodiments, the calcination temperature is 400-600° C., and the calcination time is 5-8 h.

[0007] In some of the embodiments, the step of mixing the aluminum source, carbon nanotubes and the positive electrode includes mixing at a rotation speed of 800-1200 rpm for 1-3 min, mixing at a rotation speed of 1800-2200 rpm for 2-4 min, and mixing at a rotation speed of 3200-3800 rpm for 12-18 min.

[0008] In some embodiments, the aluminum source is at least one of aluminum oxide, aluminum hydroxide, aluminum chloride, and aluminum sulfate.

[0009] In some embodiments, the positive electrode has a chemical formula of Li 1+y (Ni a Co b Al 1-a-b-c Zr c ) 1-y O2, where 0≤y≤0.2, 0.7≤a≤0.95, 0.01≤b≤0.1, 0≤c≤0.05.

[0010] In some of the embodiments, the method for preparing the positive electrode includes mixing and calcining a lithium source, a nickel-cobalt precursor, an aluminum source and a zirconium source.

[0011] Preferably, the lithium source includes at least one of lithium hydroxide, lithium carbonate or lithium acetate.

[0012] Preferably, the zirconium source is at least one of zirconium oxide, zirconium sulfate, zirconium nitrate or zirconium fluoride.

[0013] In some of the embodiments, in the preparation method of the positive electrode, the calcination step is to calcine the raw material at 400-600°C for 3-5h at a heating rate of 2-5°C / min, and then calcine at 710-750°C for 8-12h at a heating rate of 2-5°C / min.

[0014] In some of the embodiments, the step of mixing the lithium source, the nickel-cobalt precursor, the aluminum source and the zirconium source includes mixing at 800-1200 rpm for 1-3 min, mixing at 1800-2200 rpm for 2-4 min, and mixing at 3200-3800 rpm for 12-18 min.

[0015] In some embodiments, the specific surface area of ​​the nickel-cobalt precursor is 5-10 m 2 / g.

[0016] In some embodiments, the tap density of the nickel-cobalt precursor is 1-3 g / cm 3 .

[0017] In some of the embodiments, the nickel-cobalt precursor includes first grains and second grains, and the mass ratio of the first grains to the second grains is (6-8):(2-4), wherein the median particle size of the first grains is 13 to 16 μm, and the median particle size of the second grains is 2 to 4 μm.

[0018] In some of the embodiments, the total ratio of the first crystal to the second crystal in the nickel-cobalt precursor is 1:0.9-1.2.

[0019] Meanwhile, the present invention also provides a surface-modified positive electrode, which is prepared by the surface modification method of the positive electrode.

[0020] The technical solution of the present invention has the following advantages:

[0021] 1. The surface modification method of the positive electrode provided by the present invention comprises the following steps: mixing an aluminum source, carbon nanotubes and a positive electrode, and calcining to obtain a surface-modified positive electrode, wherein the addition amount of the aluminum source is 300ppm-900ppm, and the addition amount of the carbon nanotubes is 300ppm-900ppm, based on the mass of the positive electrode. The present invention utilizes carbon nanotubes and an aluminum source to coat the positive electrode material to achieve surface modification of the positive electrode material. On the one hand, it can isolate the positive electrode material from contact with the electrolyte to a large extent, thereby improving the cycle performance of the material. On the other hand, the mixture formed by the carbon nanotubes and the aluminum source has fast ion and good electron transport performance, can improve the migration rate of lithium ions, and can be used to reduce the DC resistance of the positive electrode material, while inhibiting the growth of the DC resistance during the cycle.

[0022] 2. The surface modification method of the positive electrode provided by the present invention comprises mixing and calcining a lithium source, a nickel-cobalt precursor, an aluminum source and a zirconium source. The present invention reduces the nickel content of the nickel-cobalt-aluminum positive electrode material by aluminum doping, and has minimal effect on the capacity while maintaining a stable structure. At the same time, a small amount of zirconium doping will not change the material structure, but can reduce the cation mixing inside the material, improve the structural stability, improve the cycle performance, and reduce the DC resistance of the material and the side reactions inside the material, and increase the lithium ion deintercalation rate.

[0023] 3. The surface modification method of the positive electrode provided by the present invention, the nickel-cobalt precursor includes a first crystal grain and a second crystal grain, the mass ratio of the first crystal grain to the second crystal grain is 6-8:2-4, wherein the median particle size of the first crystal grain is 13-16 μm, and the median particle size of the second crystal grain is 2-4 μm. The present invention uses mixed sintering of large and small particle precursors to further reduce the DC resistance of the material, improve the cycle performance, reduce the transmission distance of ion deintercalation, and significantly improve the kinetic rate of electron and ion transport, storage and reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 is a microscopic morphology of the surface-modified positive electrode in Example 1 of the present invention;

[0026] Figure 2 It is a cycle performance diagram of Example 1 and Comparative Example 1 in the experimental examples of the present invention. DETAILED DESCRIPTION

[0027] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0028] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0029] Example 1

[0030] This embodiment provides a surface-modified positive electrode, and the specific steps and parameters are as follows:

[0031] (1) Weigh 700g of the first grain and 300g of the second grain Ni 0.90 Co 0.10 (OH)2 precursor, 454.5g lithium hydroxide, 11.165g Al2O3 and 1.805g ZrO2, the above raw materials are mixed evenly with a high-speed mixer, the speed is set to 1000r / min for mixing for 2min, then the speed is set to 2000r / min for mixing for 3min, and the speed is set to 3500r / min for mixing for 15min, without setting a waiting time in between, to obtain the first mixed powder.

[0032] Among them, Ni 0.90 Co 0.10 The total amount of (OH)2 precursor is 10.624 mol / kg for the second particle, and the specific surface area is 7.58 m 2 / g, tap density is 1.90g / cm 3 The median particle size D50 is 2.86 μm; the first particle weight is 10.603 mol / kg, and the specific surface area is 9.08 m 2 / g, tap density is 2.15g / cm 3 The median particle size D50 is 14.58 μm, the net content of lithium hydroxide is 57.68%, and the net content of aluminum oxide and zirconium oxide is above 99.9%.

[0033] (2) The first mixed powder in step S1 is heated to 500°C at a heating rate of 2°C / min in a box furnace, kept at 500°C for 4 hours, and then heated to 725°C at a heating rate of 2°C / min, kept at 725°C for 10 hours. The sintering atmosphere is oxygen at a flow rate of 2L / min, and naturally cooled to room temperature, and crushed, and sieved through a filter with a pore size of 45μm to obtain a sintered material.

[0034] (3) Weigh 500 g of a sintered material, 0.257 g of carbon nanotubes and 0.4724 g of aluminum oxide, mix the above materials in a high-speed mixer, set the speed to 1000 r / min for mixing for 2 min, then set the speed to 2000 r / min for mixing for 3 min, set the speed to 3500 r / min for mixing for 15 min, and do not set a waiting time in between to obtain a second mixed powder.

[0035] The second mixed powder was calcined in a box furnace with oxygen as the atmosphere. The temperature was raised to 500°C at a heating rate of 2°C / min and kept at that temperature for 6 hours. After natural cooling and sieving, a surface-modified positive electrode was obtained.

[0036] The surface modified positive electrode microscopic morphology of this embodiment is shown in Figure 1 .

[0037] Example 2

[0038] This embodiment provides a surface-modified positive electrode, and the specific steps and parameters are the same as those of Embodiment 1, except that in step (1), the mass ratio of the first crystal grain to the second crystal grain is 8:2.

[0039] Example 3

[0040] This embodiment provides a surface-modified positive electrode, and the specific steps and parameters are the same as those of Embodiment 1, except that in step (1), the mass ratio of the first crystal grain to the second crystal grain is 6:4.

[0041] Example 4

[0042] This embodiment provides a surface-modified positive electrode, and the specific steps and parameters are the same as those of Embodiment 1, except that zirconium oxide is not added in step (1).

[0043] Example 5

[0044] This embodiment provides a surface-modified positive electrode, and the specific steps and parameters are the same as those of Embodiment 1, except that in step (3), based on the mass of a sintered material, the amount of carbon nanotubes added is 300 ppm, and the amount of aluminum oxide added is 300 ppm.

[0045] Example 6

[0046] This embodiment provides a surface-modified positive electrode, and the specific steps and parameters are as follows:

[0047] (1) Weigh 700g of the first grain and 300g of the second grain Ni 0.90 Co 0.10 (OH)2 precursor, 301.5g lithium carbonate, 15.21 aluminum hydroxide and 1.805g ZrO2, the above raw materials are mixed evenly using a high-speed mixer, the speed is set to 800r / min for mixing for 2min, then set the speed to 2200r / min for mixing for 4min, and set the speed to 3200r / min for mixing for 18min, without setting a waiting time in between, to obtain the first mixed powder.

[0048] Among them, Ni 0.90 Co 0.10 The total amount of (OH)2 precursor is 12.68 mol / kg for the second particle, and the specific surface area is 8.63 m 2 / g, tap density is 1.79g / cm 3 The median particle size D50 is 2.5 μm; the first particle weight is 10.578 mol / kg, and the specific surface area is 9.12 m 2 / g, tap density is 2.65g / cm 3 , the median particle size D50 is 13.12μm.

[0049] (2) The first mixed powder in step S1 is heated to 600°C at a heating rate of 5°C / min in a box furnace, kept at 600°C for 3 hours, and then heated to 710°C at a heating rate of 5°C / min, kept at 710°C for 12 hours. The sintering atmosphere is oxygen at a flow rate of 2L / min, and naturally cooled to room temperature, and crushed, and sieved through a filter with a pore size of 45μm to obtain a sintered material.

[0050] (3) Weigh 500 g of a sintered material, 0.257 g of carbon nanotubes and 0.4724 g of aluminum hydroxide, mix the above materials in a high-speed mixer, set the speed to 800 r / min for mixing for 3 min, then set the speed to 1800 r / min for mixing for 4 min, set the speed to 3200 r / min for mixing for 18 min, and set no waiting time in between to obtain a second mixed powder.

[0051] The second mixed powder was calcined in a box furnace with oxygen as the atmosphere. The temperature was raised to 400°C at a heating rate of 2°C / min and kept at that temperature for 8 hours. After natural cooling and sieving, a surface-modified positive electrode was obtained.

[0052] Example 7

[0053] This embodiment provides a surface-modified positive electrode, and the specific steps and parameters are as follows:

[0054] (1) Weigh 700g of the first grain and 300g of the second grain Ni 0.90Co 0.10 (OH)2 precursor, 454.5g lithium hydroxide, 11.165g Al2O3 and 1.805g ZrO2, the above raw materials are mixed evenly with a high-speed mixer, the speed is set to 1200r / min for mixing for 1min, then the speed is set to 2200r / min for mixing for 2min, and the speed is set to 3800r / min for mixing for 1min, without setting a waiting time in between, to obtain the first mixed powder.

[0055] Among them, Ni 0.90 Co 0.10 The total amount of (OH)2 precursor is 10.608 mol / kg for the second particle, and the specific surface area is 7.58 m 2 / g, tap density is 1.90g / cm 3 The median particle size D50 is 3.8 μm; the first particle weight is 10.629 mol / kg, and the specific surface area is 9.62 m 2 / g, tap density is 2.76g / cm 3 The median particle size D50 is 13.21 μm, the net content of lithium hydroxide is 57.68%, and the net content of aluminum oxide and zirconium oxide is above 99.9%.

[0056] (2) The first mixed powder in step S1 is heated to 400°C at a heating rate of 5°C / min in a box furnace, kept at 400°C for 5 hours, and then heated to 750°C at a heating rate of 2°C / min, kept at 750°C for 8 hours. The sintering atmosphere is oxygen at a flow rate of 2L / min, and naturally cooled to room temperature, and crushed, and sieved through a filter with a pore size of 45μm to obtain a sintered material.

[0057] (3) Weigh 500 g of a sintered material, 0.257 g of carbon nanotubes and 0.4724 g of aluminum oxide, mix the above materials in a high-speed mixer, set the speed to 1200 r / min for mixing for 1 min, then set the speed to 2200 r / min for mixing for 2 min, and set the speed to 3800 r / min for mixing for 12 min, without setting a waiting time in between to obtain a second mixed powder.

[0058] The second mixed powder was calcined in a box furnace with oxygen as the atmosphere. The temperature was raised to 400°C at a heating rate of 2°C / min and kept at that temperature for 8 hours. After natural cooling and sieving, a surface-modified positive electrode was obtained.

[0059] Comparative Example 1

[0060] This comparative example provides a surface-modified positive electrode, and the specific steps and parameters are the same as those of Example 1, except that step (3) does not contain carbon nanotubes and aluminum oxide.

[0061] That is, (3) weigh 500 g of a burning material and mix it in a high-speed mixer, set the speed to 1000 r / min and mix for 2 min, then set the speed to 2000 r / min and mix for 3 min, set the speed to 3500 r / min and mix for 15 min, without setting a waiting time in between to obtain a second mixed powder.

[0062] The second mixed powder was calcined in a box furnace with oxygen as the atmosphere. The temperature was raised to 500°C at a heating rate of 2°C / min and kept at that temperature for 6 hours. After natural cooling and sieving, a surface-modified positive electrode was obtained.

[0063] Comparative Example 2

[0064] This comparative example provides a surface-modified positive electrode, and the specific steps and parameters are the same as those of Example 1, except that step (3) does not contain carbon nanotubes.

[0065] That is, (3) 500 g of a sintered material and 0.257 g of carbon nanotubes are weighed and mixed in a high-speed mixer, and the speed is set to 1000 r / min for mixing for 2 min, then set the speed to 2000 r / min for mixing for 3 min, and set the speed to 3500 r / min for mixing for 15 min, without setting a waiting time in between to obtain a second mixed powder.

[0066] The second mixed powder was calcined in a box furnace with oxygen as the atmosphere. The temperature was raised to 500°C at a heating rate of 2°C / min and kept at that temperature for 6 hours. After natural cooling and sieving, a surface-modified positive electrode was obtained.

[0067] Comparative Example 3

[0068] This comparative example provides a surface-modified positive electrode, and the specific steps and parameters are the same as those of Example 1, except that step (3) does not contain aluminum oxide.

[0069] (3) Weigh 500 g of a sintered material and 0.4724 g of alumina, mix the above materials in a high-speed mixer, set the speed to 1000 r / min for mixing for 2 min, then set the speed to 2000 r / min for mixing for 3 min, set the speed to 3500 r / min for mixing for 15 min, and do not set a waiting time in between to obtain a second mixed powder.

[0070] The second mixed powder was calcined in a box furnace with oxygen as the atmosphere. The temperature was raised to 500°C at a heating rate of 2°C / min and kept at that temperature for 6 hours. After natural cooling and sieving, a surface-modified positive electrode was obtained.

[0071] Comparative Example 4

[0072] This comparative example provides a surface-modified positive electrode, and the specific steps and parameters are the same as those of Example 1, except that in step (3), the amount of carbon nanotubes added is 1000 ppm, and the amount of aluminum oxide added is 1000 ppm, based on the mass of the sintered material.

[0073] Comparative Example 5

[0074] This comparative example provides a surface-modified positive electrode, and the specific steps and parameters are the same as those of Example 1, except that in step (3), based on the mass of one sintered material, the added amount of carbon nanotubes is 200 ppm, and the added amount of aluminum oxide is 200 ppm.

[0075] Comparative Example 6

[0076] This comparative example provides a surface-modified positive electrode, and the specific steps and parameters are the same as those of Example 1, except that an equal mass of acetylene black is used to replace the carbon nanotubes in step (3).

[0077] Experimental example

[0078] The surface-modified positive electrodes prepared in Examples 1-7 and Comparative Examples 1-5 were respectively subjected to electrical performance tests according to the following methods, specifically: the positive electrode material, polyvinylidene fluoride, and conductive carbon black were homogenized according to a mass ratio of 95:3:2, and then the aluminum foil was spread flat on a coating machine for coating (surface density 13.3-13.5 mg / cm 2 , compacted density 3.4-3.6mg / cm 2 ), put it into an 80℃ forced air drying oven and dry it for 3h; then punch, weigh, bake the electrode and make it into a button battery.

[0079] When the cut-off voltage is in the range of 2.5V-4.25V, the charging and discharging process is the first cycle (0.2C / 0.2C), the second cycle (0.2C / 1C), the third cycle (0.2C / 1C), and the fourth to the 53rd cycle (1C / 1C), and the electrical performance test is carried out using the blue electric test system.

[0080] At the same time, the voltage of 10-second 1C discharge is increased in the 53rd cycle, and the DC resistance (DCR) value of the button battery is obtained by using the voltage / current.

[0081] The results are shown in Table 1.

[0082] Table 1 Button battery performance test results

[0083]

[0084] According to Table 1, compared with the technical solution of comparative example 1 in which the positive electrode is not coated with an aluminum source or carbon nanotubes, comparative examples 2-3 in which only one of the aluminum source or carbon nanotubes is used to coat the positive electrode, or comparative example 6 in which acetylene black is used instead of carbon nanotubes, the positive electrode is coated with an aluminum source and carbon nanotubes provided in the embodiment of the present invention, which can significantly reduce the DC resistance, increase the first discharge capacity and improve the capacity retention rate. Furthermore, compared with comparative examples 4-5 in which the addition amount of carbon nanotubes and aluminum sources is 200ppm or 1000ppm, the performance of reducing the DC resistance, increasing the first discharge capacity and improving the capacity retention rate is not as good as that of the addition amount of 300-800ppm.

[0085] according to Figure 2 It can be seen that the surface-modified positive electrode provided in Example 1 of the present invention has better cycle performance than the positive electrode provided in Comparative Example 1.

[0086] Furthermore, compared with Example 4 of the present invention, the present invention significantly improves the material by doping zirconium elements in the positive electrode material. This may be because as the charge and discharge proceed, a certain amount of doped zirconium ions may also migrate to the electrode surface and form a solid solution, preventing the structural collapse caused by the anisotropic structural change during charge and discharge. At the same time, the solid solution also acts as a protective coating to prevent cobalt from dissolving into the electrolyte. Therefore, the material structure becomes very stable during the phase change of the cycle process, and the cycle stability is enhanced. At the same time, the particle size of the material becomes smaller after ZrO2 doping, and the material is easier to deintercalate during the charge and discharge process after the particle size becomes smaller, so the discharge specific capacity of the doped material increases.

[0087] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for surface modification of a positive electrode, characterized in that: The following steps are included: The aluminum source, carbon nanotubes and positive electrode are mixed and calcined to obtain a surface-modified positive electrode. Based on the mass of the positive electrode, the added amount of the aluminum source is 300ppm-900ppm, and the added amount of the carbon nanotubes is 300ppm-900ppm.

2. The surface modification method of the positive electrode according to claim 1, characterized in that: The calcination temperature is 400-600°C and the calcination time is 5-8h; and / or, The step of mixing the aluminum source, carbon nanotubes and the positive electrode includes mixing at a rotation speed of 800-1200 rpm for 1-3 minutes, mixing at a rotation speed of 1800-2200 rpm for 2-4 minutes, and mixing at a rotation speed of 3200-3800 rpm for 12-18 minutes.

3. The surface modification method of the positive electrode according to claim 2, characterized in that: The aluminum source is at least one of aluminum oxide, aluminum hydroxide, aluminum chloride and aluminum sulfate; and / or The chemical formula of the positive electrode is Li 1+y (Ni a Co b Al 1-a-b-c Zr c ) 1-y O2, where 0≤y≤0.2, 0.7≤a≤0.95, 0.01≤b≤0.1, 0≤c≤0.

05.

4. The surface modification method of the positive electrode according to claim 3, characterized in that: The preparation method of the positive electrode comprises mixing and calcining a lithium source, a nickel-cobalt precursor, an aluminum source and a zirconium source.

5. The surface modification method of the positive electrode according to claim 4, characterized in that: In the preparation method of the positive electrode, the calcination step is to calcine the raw material at 400-600°C for 3-5h at a heating rate of 2-5°C / min, and then calcine at 710-750°C for 8-12h at a heating rate of 2-5°C / min; and / or, The step of mixing the lithium source, the nickel-cobalt precursor, the aluminum source and the zirconium source includes mixing at a rotation speed of 800-1200 rpm for 1-3 min, mixing at a rotation speed of 1800-2200 rpm for 2-4 min, and mixing at a rotation speed of 3200-3800 rpm for 12-18 min.

6. The surface modification method of the positive electrode according to any one of claims 4 to 5, characterized in that: The specific surface area of ​​the nickel-cobalt precursor is 5-10m 2 / g; and / or, The tap density of the nickel-cobalt precursor is 1-3 g / cm 3 .

7. The surface modification method of the positive electrode according to any one of claims 4 to 6, characterized in that: The nickel-cobalt precursor includes first crystal grains and second crystal grains, wherein the mass ratio of the first crystal grains to the second crystal grains is 6-8:2-4, wherein the median particle size of the first crystal grains is 13-16 μm, and the median particle size of the second crystal grains is 2-4 μm.

8. The surface modification method of the positive electrode according to claim 7, characterized in that: The total ratio of the first crystal to the second crystal in the nickel-cobalt precursor is 1:0.9-1.

2.

9. The surface modification method of the positive electrode according to any one of claims 4 to 8, characterized in that: The lithium source includes at least one of lithium hydroxide, lithium carbonate or lithium acetate; and / or, The zirconium source is at least one of zirconium oxide, zirconium sulfate, zirconium nitrate or zirconium fluoride.

10. A surface-modified positive electrode, characterized in that: A positive electrode obtained by the surface modification method of the positive electrode according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Composite modified lithium ion battery cathode material and preparation method thereof

    CN104617303A

  • Metallic oxide-coated modified doped ternary anode material and preparation method thereof

    CN105118967A

  • High-voltage and single-crystal ternary positive electrode material and preparation method thereof

    CN107293744A

  • Al2O3 coated NCA ternary cathode material for lithium ion battery, preparation method and application

    CN108428873A

  • High-capacity monocrystal-like lithium nickel cobalt aluminate positive electrode material and preparation method thereof

    CN109449391A

Cited By

  • Positive electrode material and preparation method thereof

    CN120600788A